2015
DOI: 10.1016/j.bmc.2015.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl sulfone analogs of lysophosphatidylcholine irreversibly inhibit autotaxin and prevent angiogenesis in melanoma

Abstract: Autotaxin (ATX) is an enzyme discovered in the conditioned medium of cultured melanoma cells and identified as a protein that strongly stimulates motility. This unique ectonucleotide pyrophosphatase and phosphodiesterase facilitates the removal of a choline headgroup from lysophosphatidylcholine (LPC) to yield lysophosphatidic acid (LPA), which is a potent lipid stimulator of tumorigenesis. Thus, ATX has received renewed attention because it has a prominent role in malignant progression with significant transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Additional studies suggest that serum measurements of autotaxin concentration may be useful as a biomarker for follicular lymphoma [41]. Within the tumor microenvironment, autotaxin is found where tumor cells are undergoing angiogenesis [42], due to its normal role in vasculogenesis [43,44]. In general, inhibiting autotaxin through chemical means or siRNA delivery will kill cells and prevent metastatic progression, in vitro and in vivo [34,42,45,46,47,48].…”
Section: Overview Of Lysophosphatidic Acid Signaling and Autotaxinmentioning
confidence: 99%
“…Additional studies suggest that serum measurements of autotaxin concentration may be useful as a biomarker for follicular lymphoma [41]. Within the tumor microenvironment, autotaxin is found where tumor cells are undergoing angiogenesis [42], due to its normal role in vasculogenesis [43,44]. In general, inhibiting autotaxin through chemical means or siRNA delivery will kill cells and prevent metastatic progression, in vitro and in vivo [34,42,45,46,47,48].…”
Section: Overview Of Lysophosphatidic Acid Signaling and Autotaxinmentioning
confidence: 99%
“…The conduct of further in vivo studies in a xenograft melanoma experimental animal model demonstrated that 18 significantly inhibited tumor progression at 40 to 50 mg/kg dose after 65 days, exerting also a superior efficacy compared with other known and potent ATX inhibitors. Of interest, the mechanism through which 18 exhibited its antitumor effect was by preventing angiogenesis and not by inhibiting mitogenesis as initially thought based on the in vitro data results . However, health deterioration of the subjects and unexpected death of one of them during the study cast doubts about the safety profile of this class of inhibitors and its therapeutic potential against melanoma progression.…”
Section: Inhibitors Of Atxmentioning
confidence: 99%
“…In an interesting example of inhibitor design, a small series of vinyl sulfone derivatives was recently prepared by Georgia University, as part of a broader effort to explore the possibility of identifying irreversible ATX inhibitors (Figure ) . The concept of developing irreversible ATX inhibitors is supported by the presence of a critical threonine residue in the catalytic site of the enzyme (Thr 210 ) acting as a nucleophile in the hydrolysis of LPC to LPA and choline.…”
Section: Inhibitors Of Atxmentioning
confidence: 99%
See 2 more Smart Citations